Self‐help educational booklets for the prevention of smoking relapse following smoking cessation treatment: a randomized controlled trial - Maskrey, Vivienne; Blyth, Annie; Brown, Tracey J.; Barton, Garry R.; Notley, Caitlin; Aveyard, Paul; Holland, Richard; Bachmann, Max O.; Sutton, Stephen; Leonardi-Bee, Jo (Wiley, 2015)
Aims: Most people who quit smoking for a short term will return to smoking again in 12 months. We tested whether self-help booklets can reduce relapse in short-term quitters after receiving behavioural and pharmacological cessation treatment.